(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The legality of slavery in Brazil had its end in 1888. However, it continued to be practiced clandestinely, because to this day people are rescued in conditions analogous to slavery. The restriction of freedom has been one of the characteristics of slavery since the colonial and imperial periods, since the worker is tied to it for his entire life. However, it should be mentioned that slave labor, in contemporary times, is not only characterized by the restriction of workers’ freedom, but also by the absence of respect for their dignity and integrity. In this perspective, it is necessary to ask whether contemporary Brazilian slavery violates the constitutional principle of the dignity of the human person? In search of an answer, the research, which follows the method of deductive approach and methods of historical and bibliographic procedure, indicates that yes, dignity is undermined by the practice of slave labor in the country, even if, at times, the means employed to maintain someone as a slave may be more discreet than before, which does not make the conduct any less serious.